Philosophy of Creativity - Hanna, Taran; Ivan, Chornomordenko (KNUCA, 2026)
Contains the topics of lectures and seminars on the course "Philosophy of Creativity". Scientific and educational change structured according to the curriculum programs of this course and consists of on the topics of lecture and seminar classes, theoretical thematic tasks, list final questions and topics of essays. Intended for the discipline for applicants of the second (master's) level of higher education in the specialty В2 "Design". Містять тематику лекційних та семінарських занять з курсу «Філософія творчості». Науково-освітній зміст структуровано відповідно до навчальної програми курсу і складається з тематики лекційних та семінарських занять, теоретичних тематичних завдань, переліку підсумкових питань та тематики рефератів. Призначено для здобувачів другого (магістерського) рівня вищої освіти спеціальності В2 «Дизайн» які навчаються англійською мовою.
Філософія творчості
Keywords: 1:72.012